Proximal hypospadias repair with bladder mucosal graft: Our 10 years experience. Issue 3 (June 2017) - Lanciotti, Michele; Betti, Marta; Elia, Antonio; Landi, Luca; Taverna, Maria; Cini, Chiara; Masieri, Lorenzo
Summary: Introduction and objective: A great variety of different surgical techniques has been described for proximal hypospadias repair and an ideal tissue has not been determined yet. We present our 10 years of surgical experience using a bladder mucosal graft for urethroplasty. Study design: Bladder mucosal graft urethroplasty was performed between 2005 and 2015 in 50 patients with severe proximal hypospadias. The mean age of patients was 45.1 months (range 24–164 months). Hypospadias were perineal in 18 patients, scrotal in 22, and penoscrotal in 10. In all cases a chordee correction was performed and median time between the first and the second stages was 12 months (mean 17 months, range 4–68 months). Both foley catheter and a suprapubic cystostomy were positioned and maintained for 2–4 weeks. Follow-up was performed at 1–3 and 6–12 months after surgery, and afterwards annually with clinical examination and flowmetry test. Results: Mean follow-up was 5.3 years (median 5, range 1–10 years). Mean graft length was 57.4 mm (median 55 mm, range 35–85 mm). Among all the only early complication registered was a postoperative infection in one patient (2%) at the site of anastomosis. The long-term complications observed were urethrocutaneous fistula in nine patients (18%), urethral stricture in 15 patients (30%), meatal stricture in four patients (8%), and prolapse of meatus in seven patients (14%). The mean time of complication occurrence was 15 months (median 15.5 months, range 1–96 months). The functional and cosmetic appearance after surgery was satisfactory in 42/50 patients (84%) during the follow-up period. Discussion: There is still an open debate regarding the optimal surgical approach for management of severe proximal hypospadias. Compared with other approaches, our technique showed acceptable results even though encumbered by slightly higher complication rates. Conclusion: Our results show that bladder mucosal graft for primary severe proximal hypospadias in selected patients is a possible alternative to other commonly used techniques, with the aim of restoring recovery of the normal continuity of the distal urinary tract see figure below. Figure Urethral micturition after bladder graft mucosa urethroplasty.